Observation of strong excitonic magneto-chiral anisotropy in twisted bilayer van der Waals crystals - Shoufeng Lan (Nature Portfolio, 2021)
Systems where both time-reversal symmetry and inversion symmetry are broken can exhibit a magneto-chiral effect; however, this is usually weak. Here, Lan et al demonstrate a significantly enhanced excitonic magnetochiral effect in twisted bilayer tungsten disulphide on a ferromagnetic substrate.